Satisfação e continuidade do uso do DIU de cobre pós-cesárea - Albuquerque, Clarisse Uchoa de (2020)
The insertion of the cesarean postpartum intrauterine device (IUD) immediately defined as the insertion of the IUD within 10 minutes after the removal of the placenta. It is an attractive strategy in a country with high rates of cesarean sections and rates of unplanned pregnancies to increase access to long-acting reversible contraceptives (LARCs), as it does not require a return visit to initiate contraception. The study was designed to assess adherence, satisfaction and satisfaction of patients with a desire for postpartum contraception who introduced copper IUDs during cesarean delivery. A prospective study was carried out involving 158 patients who underwent copper IUD insertion during cesarean section at Maternidade Escola Assis Chateaubriand. The IUD offered after admission to the participant in the selected patients according to the eligibility criteria. The women were followed up on an outpatient basis 6 weeks after insertion of the IUD, when the satisfaction questionnaire and complications were completed; and after 6 months via teleconsultation. The evaluation of the positioning of the IUD was performed through transvaginal ultrasound approximately 40 days after insertion. IUD continuation rates after 6 weeks and after 6 months were 92% and 71.5%, respectively, as well as expulsion rates up to 6 weeks was 0.6% and up to 6 months after insertion was 1, 3%. The rate of removal of the IUD at the patient's request was higher after 6 weeks (8.2%) than before 6 weeks after insertion (1.9%). The rate of misplaced IUDs was 5% and the visible thread rate at the 6-week consultation was 29.1%, both without association with age, parity, gestational age, uterine volume or active labor (PT). There were 2 cases of infection (1.3%) and no case of perforation or pregnancy. The most reported side effects were pelvic pain (10.7%) and bleeding (6.3%). In the 6-week consultation, 85% of patients were satisfied with the method and 76% at 6 months. An immediate postpartum IUD insertion protocol was developed and instituted at the end of the study. There was a good rate of continuation and satisfaction with the immediate post-partum cesarean IUD and a low rate of complications. There was no association between malpositioning of the device and visible IUD wire with age, parity, gestational age, uterine volume or active labor.